Apelin Rejuvenates Aged Human Mesenchymal Stem Cells by Regulating Autophagy and Improves Cardiac Protection After Infarction - Zhang, Hao; Zhao, Chengling; Jiang, Guojun; Hu, Bei; Zheng, Huifeng; Hong, Yimei; Cui, Zhen; Shi, Linli; Li, Xin; Lin, Fang; Ding, Yue; Wei, Lu; et al. (Frontiers in Cell and Developmental Biology, 2021)
The protective effects of mesenchymal stem cell (MSC)-based therapy for myocardial infarction (MI) are largely hampered as they age. Apelin is an endogenous ligand of its receptor APJ and plays an essential role in regulating multiple biological activities including MSC proliferation and survival. In this study, we investigated whether Apelin regulates MSC senescence and whether its overexpression could rejuvenate aged MSCs (AMSCs) to improve cardiac protection following infarction in mice. MSC senescence was evaluated by senescence-associated β-galactosidase assays. Apelin level was examined by western blotting. Autophagy was determined by transmission electron microscopy. The cardioprotective effect of AMSCs with Apelin overexpression (Apelin-AMSCs) was assessed in a mouse MI model. Apelin expression was dramatically reduced in AMSCs. Interestingly, knockdown of Apelin induced young MSCs (YMSC) senescence, whereas overexpression rescued AMSC senescence. Apelin overexpression also increased AMSC angiogenic capacity. Mechanistically, Apelin overexpression upregulated the autophagy level of AMSCs by activating AMP-activated protein kinase (AMPK) signaling, thereby rejuvenating AMSCs. Compared with AMSCs, transplantation of Apelin-AMSCs achieved better therapeutic efficacy for MI by enhancing cell survival and angiogenesis. In conclusion, our results reveal that Apelin activates AMPK to rejuvenate AMSCs by increasing autophagy and promotes cardioprotection following infarction in mice. This study identified a novel target to rejuvenate AMSCs and enhance their therapeutic efficacy.